NPRC 2023: Faculty of Business and Management, UiTM Puncak Alam organized the 2nd National Pitching Research Competition (NPRC)– final stage - UiTM, Faculty of Business and Management (UiTM, 2023)
The Faculty of Business and Management, UiTM Puncak Alam, successfully organized the final stage of the 2nd National Pitching Research Competition (NPRC) 2023, providing a platform for students and young researchers to present their research ideas, receive expert feedback, and promote innovation and creativity.